Sistem Informasi Berbasis Web Pembayaran SPP Di SMA RK BT Rantau Prapat - Saragih, Reagan; Manalu, Dudes; Hardinata, Jaya Tata (Jurnal Gemilang Informatika (GIT), 2023)
The use of computer technology at this time is needed, especially in the field of data processing, both for the benefit of individuals and agencies. tuition fee is a contribution to education development which means that donations are in the form of funds for educational development within an educational institution. Currently, most of the educational institutions in processing the payment data for tuition fee, student council, school equipment, are still by recording in the ledger including the tuition fee payment system at SMA RK Bintang Timur Rantau Prapat. From the problems above, the authors create a payment data processing system that aims to build a payment data processing system that is easy to use and reliable and ensures data availability. The results of this study are in the form of a payment system that can be implemented at SMA RK Bintang Timur Rantau Prapat, or educational institutions, which can eventually be used for storage, processing, and reporting of computerized payment data, in providing services and the performance of school fee payments can run well, and can speed up the service of data information for parties in need such as students, the finance department and reports to the principal. Kata kunci: tuition fee payment system, PHP, Mysql, Javascript, CSS